Workflow: success or failure. - Tan, Tian Leng. (2008)
This project seeks to evaluate the success of workflow through clarifying its fuzzy notion by proposing an integrated framework and examining the mixed views of users. Four applications of workflow are analysed and possible future trends are predicted.